Enhancing early childhood creativity through loose-parts media based on STEAM learning - Ayu Citra Dewi; Alif Laini; Sri Intan Wahyuni; Mega Cahya Dwi Lestari (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
This article examines classroom action research in which researchers and classroom teachers collaborate to understand and improve the benefits of loose-part media to increase children's creativity and the subsequent impact of loose-part media based on STEAM learning. Focusing on early childhood education, this research was carried out in collaboration with teachers provided 21 pupils 5–6-year-old at Mutiara Kasih Kindergarten in Padang City. The research procedures carried out included a combination of observation, discussion and reflection on practice in 3 cycles. Loose-part media based on STEAM learning is considered to have increased children's creativity, as shown by pre-cycle data of 6.9%. Cycle I was carried out with a creativity percentage of 15.4%, increasing to 47.1% after cycle II, and increasing to 80.42% after cycle III. This research recommends that the use of loose-parts and utilizing the surrounding environment based on STEAM learning can be implemented in kindergarten institutions.